2019
DOI: 10.1038/s41419-019-1428-1
|View full text |Cite
|
Sign up to set email alerts
|

Mmu-miR-185 depletion promotes osteogenic differentiation and suppresses bone loss in osteoporosis through the Bgn-mediated BMP/Smad pathway

Abstract: MicroRNAs (miRs) play an essential role in the regulation of bone formation and homeostasis. miR-185 has been reported to negatively regulate osteogenesis in vitro. However, whether it has an impact on in vivo bone homeostasis remains unknown. Here, we demonstrated that primary osteoblasts and mesenchymal stem cells derived from miR-185-knockout (KO) mice exhibited enhanced osteogenesis. Further, we constructed an ovariectomized mouse model to investigate the role of miR-185 during osteoporosis. Micro-computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 28 publications
3
62
0
Order By: Relevance
“…Dysfunctional miRNAs in osteoporosis have been proven to exert a certain therapeutic potential. Bone destruction and strength are greatly improved in osteoporosis mice intravenously administrated with chemically synthesized miR-106b-5p, miR-17-5p, or miR-451 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctional miRNAs in osteoporosis have been proven to exert a certain therapeutic potential. Bone destruction and strength are greatly improved in osteoporosis mice intravenously administrated with chemically synthesized miR-106b-5p, miR-17-5p, or miR-451 [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that overexpression of miR185 can lead to a signi cant reduction in lipid accumulation, while the low level of miR185 can promote adipogenic differentiation [32] . Studies have demonstrated that the inhibition of miR185 could promote bone formation and osteogenic differentiation [33,42,43] . In this study, it was found that the expressions of hepatic relative genes and proteins by cells overexpression of miR185 induction group were decreased compared with normal hUC-MSCs after hepatic induction differentiation, which means, differentiation of hUC-MSCs was delayed by overexpression of miR185.…”
Section: Discussionmentioning
confidence: 99%
“…Microribonucleic acids (microRNAs or miRs) are a type of single-stranded, non-coding and small-molecule RNAs approximately 18-25 nucleotides in length, which are involved in the occurrence and progression of various diseases ( 7 , 8 ). It has been reported that some miRs can participate in bone turnover, bone metabolism and bone development, thereby regulating the occurrence and progression of OP ( 9-11 ). However, whether there is a certain association between miRs and T2DM + OP has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%